Медичний туризм в Польщі: статистичний та управлінський ракурс - Гальків Любов; Halkiv Lyubov; Щука Галина; Shchuka Halyna; Scsuka Halina; Едита Мазурек; ‪Edyta Mazurek (Національний університет "Львівська політехніка", 2020)
Резюме. Досліджено динаміку та структуру в’їзного потоку міжнародних туристів до Польщі та чинники, які зумовлюють його висхідну тенденцію. Розкрито передумови, які сприяли тому, що Польща завоювала свою нішу на європейському ринку оздоровчих і лікувальних послуг. Охарактеризовано джерела статистичної інформацій про медичний туризм Польщі. Розкрито проблеми якості та доступності офіційних статистичних даних щодо кількості споживачів послуг медичного туризму. Досліджено мотиви та структуру попиту на послуги медичного туризму в Польщі. Розкрито зміни та небезпеки, з якими стикається кадровий менеджмент виробників послуг медичного туризму. Узагальнено управлінську практику суб’єктів господарювання та суспільних інституцій Польщі, яка націлена на покращення використання медичного потенціалу країни у туристичній сфері.

Abstract. The dynamics and structure of incoming flow of international tourists to Poland and the factors that determine its upward trend have been explored in this article. Preconditions, which has contributed to the fact that the Polish health care system has gained a niche in the European market for health and medical services, have been disclosed. Poland ranked 24th among the countries of the world (5th place among European countries) according the medical tourism index in 2017. Sources of statistical information on medical tourism in Poland have been characterized. The problems of accessibility (limitations) of official statistics on the number of persons receiving medical services as international tourists have been revealed. It is substantiated that, on the one hand, the practice of satisfying the demand of foreign patients from the border-zone on a number of short-term medical services in Poland and, on the other hand, medical care for persons who work abroad but officially have the status of unemployed in Poland negatively affect the quality of statistical data on international tourism. The impelling reasons to leave the country of permanent residence to receive medical services in Poland have been investigated. It has been found out that the most weighty reasons are the cost savings; insufficiency or lack of services at home; long waiting time to receive medical services back home. The geographical structure of medical tourism consumers in Poland and the factors of their demand activation have been analyzed. Changes and dangers faced by personnel management of medical tourism service providers have been revealed. The management practice of medical tourism entities aimed at creating clusters in Poland has been generalized. The main directions of public institutions activities in Poland, which contribute to improving the utilization of the country’s medical potential in the tourism sphere, have been described.
Medical tourism in Poland: statistical and management outlook
Keywords: міжнародний туризм; медичний туризм; статистика туризму; управління змінами; international tourism; medical tourism; tourism statistics; change management